Geographic Variations in Retention in Care among HIV-Infected Adults in the United States. - Peter F Rebeiro; Stephen J Gange; Michael A Horberg; Alison G Abraham; Sonia Napravnik; Hasina Samji; Baligh R Yehia; Keri N Althoff; Richard D Moore; Mari M Kitahata; Timothy R Sterling; Frank C Curriero; et al. (PLoS ONE)
Objective To understand geographic variations in clinical retention, a central component of the HIV care continuum and key to improving individual- and population-level HIV outcomes. Design We evaluated retention by US region in a retrospective observational study. Methods Adults receiving care from 2000-2010 in 12 clinical cohorts of the North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD) contributed data. Individuals were assigned to Centers for Disease Control and Prevention (CDC)-defined regions by residential data (10 cohorts) and clinic location as proxy (2 cohorts). Retention was ≥2 primary HIV outpatient visits within a calendar year, >90 days apart. Trends and regional differences were analyzed using modified Poisson regression with clustering, adjusting for time in care, age, sex, race/ethnicity, and HIV risk, and stratified by baseline CD4+ count. Results Among 78,993 adults with 444,212 person-years of follow-up, median time in care was 7 years (Interquartile Range: 4-9). Retention increased from 2000 to 2010: from 73% (5,000/6,875) to 85% (7,189/8,462) in the Northeast, 75% (1,778/2,356) to 87% (1,630/1,880) in the Midwest, 68% (8,451/12,417) to 80% (9,892/12,304) in the South, and 68% (5,147/7,520) to 72% (6,401/8,895) in the West. In adjusted analyses, retention improved over time in all regions (p<0.01, trend), although the average percent retained lagged in the West and South vs. the Northeast (p<0.01). Conclusions In our population, retention improved, though regional differences persisted even after adjusting for demographic and HIV risk factors. These data demonstrate regional differences in the US which may affect patient care, despite national care recommendations.